Haplotyping of Echinococcus granulosus Isolates From Human, Sheep and Cattles Hydatid Cysts in Some Central Euphrates Provinces, Iraq - Nabaa Zahid Sabri Shani Al-Hasnawi; Ahmed Khudhair Al-Hamairy; Huda Jasim M. Altameme (Institute of Medico-legal Publications Pvt Ltd, 2021)
This study included nine samples collected from the infected (liver and lung) divided into three equalsamples (sheep, cattle and humans) collected from some Central Euphrates Provinces for the period from thebeginning August 2019 till February 2020. PCR technique was performed for in detection and genotypingof Echiococcus granulosus hydatid cyst based on mitochondrial Cox1 gene and Nad1 genes in isolates.This technique was carried out according to method described by Nikmanesh et al. (2014). The presentstudy aimed to showed haplotype genetic and the frequency percentage of it in the Central Euphratesregion.the result showed the H15 haplotype was a higher frequency followed it ( H10, H11) and then (H5).The frequency percentage of the haplotype genetic in the current study of the taken samples (8) that theprevalence and frequency of haplotype genetic H15 was 37.5%, followed by the genotype ( H10,H11) at25% for both them , and the lowest was the genotype (H5) at 12.5% The human samples registered 100%for (H15) , the sheep registered 50 % for H5, H10.While cattle samples registered 33.3 % for H10 and 66.6for H11 . Isolation H15 is the essential in the infection to humans as a result of dogs were fed hydatid cystsof cattle origin, and there is no relationship between sheep and humans, while there is a relationship betweensheep and cattle in the Haplotype (H10).